1989
DOI: 10.1083/jcb.108.5.1673
|View full text |Cite
|
Sign up to set email alerts
|

Binding and transepithelial transport of immunoglobulins by intestinal M cells: demonstration using monoclonal IgA antibodies against enteric viral proteins.

Abstract: Abstract. M cells of intestinal epithelia overlying lymphoid follicles endocytose luminal macromolecules and microorganisms and deliver them to underlying lymphoid tissue. The effect of luminal secretory IgA antibodies on adherence and transepithelial transport of antigens and microorganisms by M cells is unknown. We have studied the interaction of monoclonal IgA antibodies directed against specific enteric viruses, or the hapten trinitrophenyl (TNP), with M cells. To produce monospecific IgA antibodies agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
2
2

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(135 citation statements)
references
References 42 publications
4
127
2
2
Order By: Relevance
“…Monoclonal IgA, polyclonal secretory IgA and IgA antigen complexes were shown to adhere selectively to M cell surfaces and transported into the intraepithelial pocket (96). In this way slgA would serve as a vaccine-targeting molecule.…”
Section: Igamentioning
confidence: 99%
“…Monoclonal IgA, polyclonal secretory IgA and IgA antigen complexes were shown to adhere selectively to M cell surfaces and transported into the intraepithelial pocket (96). In this way slgA would serve as a vaccine-targeting molecule.…”
Section: Igamentioning
confidence: 99%
“…IgA hybridomas are first generated from Peyer's patch lymphoblasts after mucosal immunization of BALB/c mice, and clones are selected for appropriate antimicrobial antigen specificities and for efficient production of dimeric IgA monoclonal antibodies in culture [10]. The hybridoma cells are injected subcutaneously on the upper backs of naive, syngeneic mice where they grow to form hybridoma tumours that release monoclonal, dimeric IgA into the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…SIgA exhibits the striking feature to adhere to the apical membrane of M cells (49,50), promoting uptake of small amounts of Ab as reflected by the detection of gold-coated SIgA in the pocket of M cells (51). Refined analysis of the interaction of M cells with Ab molecules demonstrated that IgA, with or without bound SC, but not IgG or IgM, bound selectively to murine and human M cells (52).…”
Section: Uptake Of Siga By Peyer's Patchesmentioning
confidence: 99%